STUDI KUALITAS MATA AIR PERBUKITAN PUNCAK TEMBOK DI KENAGARIAN PANINJAUAN KECAMATAN X KOTO DIATAS KABUPATEN SOLOK (JURNAL SPASIAL, 2015)
This study aims to determine: 1) quality of the physical (color, taste, temperature, odor and kekeruan, 2) quality of the chemical (pH, CaCO3 and Fe (iron), 3) Quality of biological (bacteria e coli fecal) and 4) distribution quality springs in Puncak Tembok Paninjauan village X Koto Diatas District Solok region. This type of research is a descriptive study using a survey method. The study was conducted at the District X Koto Kenagarian Paninjauan Above Solok District.The research sample consisted of 3 samples. Analysis of water quality in physics (color, smell taste and temperature) using the five senses, in the field at the time of sampling. Chemical quality of drinking water with the parameters pH, iron (Fe) and CaCO3, and the amount of biological parameters e coli fecal bacteria carried by the analysis in the laboratory. The results obtained were compared with drinking water quality standards of the Ministry of Health Regulations No. No. 492/Menkes/Per/IV/2010.  The results showed that: 1) Quality of physics (color, taste, temperature, odor and turbidity) spring hills of Puncak Tembok on the sample I qualify except the color and taste of the water because the water is yellowish and somewhat tasteless, samples II and samples II meet requirements for color, taste, odor and turbidity, 2) Quality of the chemical (pH, CaCO3 and Fe (iron) spring hills of Puncak Tembok qualify in sample 1 except Fe content, the sample 2 are eligible except Fe content, 3) the quality of biological (bacteria e coli fecal) spring hills of Puncak Tembok in sample 1 are not eligible for consumption, on the sample 2 does not qualify for consumption and the sample 3 qualify for consumption and 4) Distribution of Quality springs hills Puncak Tembok, sample I water not eligible to warn of physics quality and taste, are eligible for the chemical quality except for Fe content and is not eligible for the biological quality. In the second sample the water quality meets the requirements in terms of quality physics, qualify for the chemical quality except for Fe content and is not eligible for the biological quality. 3 water samples qualify untuak quality of physics, chemistry and biology.Key Words: quality of physical, quality of chemical, quality of biological